Hisab Dan Rukyat Dalam Penentuan Awal Bulan Qamariyah Di Indonesia Perspektif Hadis - Ahmad Muslih Haryanto (Al-Mu'tabar, 2023)
ABSTRACTThe problem of determining the beginning of the Qomariyah month using the hisab and rukyat methods has been controversial in Indonesia for a long time. This is caused by differences in views. The aim of this research is to provide an understanding regarding the methods of reckoning and rukyat from the perspective of hadith in determining the beginning of the month of Qomariyah. This research uses a library research approach with qualitative analysis methods based on data collected from hadiths related to determining the beginning of the month of Qomariyah. The analysis in this research uses content analysis to draw conclusions. The results of this research show that when referring to the hadith, when referring to the hadith, there is khilafiyah in the interpretation. This is what happens in Indonesia, in determining the beginning of the Qomariyah month, there is a difference caused by the meaning of the hadith text itself. Therefore, a textual understanding of the hadith is necessary, so that the interpretation of its meaning can be fully understood. Thus, in dealing with differences that arise, an attitude of mutual respect for each other is needed. So that the existing differences do not give rise to sentiment and division between Muslims in Indonesia.Keywords: Reckoning; Rukyat; Determination of the Beginning of the Month; Hadith ABSTRAKPermasalahan penentuan awal bulan qomariyah dengan metode hisab dan rukyat menjadi kontroversi di Indonesia sejak lama. Hal ini disebabkan oleh adanya perbedaan pandangan. Tujuan penelitian ini adalah untuk memberikan pemahamahan terkait metode hisab dan rukyat dalam pandangan hadis dalam penentuan awal bulan qomariyah. Penelitian ini menggunakan pendekatan studi kepustakaan (library research) dengan metode kualitatif analisis berdasar data yang dikumpulkan dari hadis-hadis tekait dengan penentuan awal bulan qomariyah. Adapun analisis dalam penelitian ini menggunakan content analisis guna menarik suatu kesimpulan. Hasil penelitian ini menunjukkan bahwa penentuan awal bulan qomariyah, jika merujuk pada hadis terdapat khilafiyah dalam intepretasinya. Hal ini sebagaimana yang terjadi di Indoensia, dalam penentuan awal bulan qomariyah terjadi suatu perbedaan yang disebabkan oleh pemaknaan teks hadis itu sendiri. Oleh karena itu, pemahaman tekstual hadis diperlukan, agar intepretasi pemaknaannya dapat dipahami secara utuh. Dengan demikian, dalam menghadapi perbedaan yang muncul, dibutuhkan sikap saling menghargai satu sama lain. Sehingga perbedaan yang ada tidak menimbulkan sikap sentimen dan perpecahan antar umat Islam di Indonesia.Kata Kunci: Hisab; Rukyat; Penentuan Awal Bulan; Hadis